DFT/TDDFT methods analysis of ESIPT process in a series of 7-hydroxy-1-indanone derivates and new dyad design - Yuan-Qing Lei; Jian-Ying Xi; Hao Guo; Ran Jia (Journal of Saudi Chemical Society)
In this work, DFT/TDDFT methods were utilized to have an analysis on the excited-state intramolecular proton transfer (ESIPT) in a series of 7-hydroxy-1-indanone derivates. By comparison of the relative energy in first excited state of each isomer, it is concluded that the direction of ESIPT is decided by the stability of isomer, which may be tuned by the change of conjugation pattern. Based on the results above, a strategy was proposed to control the ESIPT process, in which a dyad was designed by combining the derivate and dithienylethene together. Through the photoisomerization of dithienylethene, the excited group involved in excitation will make an effective shift, which, could act as a switch for the ESIPT process. Keywords: Photoisomerization, Dyad, Excited-state, Proton transfer